DIFFERENCES OF PHILOSOPHY, SCIENCE, AND RELIGION - Syahrullah Asyari (International Conference on Social and Islamic Studies, 2021)
Philosophy, science, and religion are three things that often become a discourse in philosophical discussions. Unfortunately, there is still limited writing that juxtaposes the differences between the three explicitly in a scientific framework. This paper seeks to justify the differences between the three explicitly in a scientific framework. Based on the results of the study of various authoritative sources on these three things, the author can state that philosophy and religion are very different. There is even a tendency for the difference to appear diametrically. Meanwhile, philosophy and science seem to have similarities and differences. Likewise, between religion and science, there are similarities and differences between the two from a certain point of view.